2013
DOI: 10.1111/j.1540-8183.2013.12016.x
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus‐Eluting Stents Versus Sirolimus‐ or Paclitaxel‐Eluting Stents: Two‐Year Results from the Guthrie Health Off‐Label Stent (GHOST) Registry

Abstract: The use of EES compared to FG-DES appears to be associated with reductions in ST and TVR at 2-year follow-up. Improved outcomes with EES are observed in comparison with SES as well as PES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Several studies have demonstrated the superiority of DES over BMS regarding the need for target-lesion revascularisation [10][11]. In agreement with previous research, in our study, BMS-ISR was significantly more frequent than DES-ISR, but without significant betweenstudy-group differences.…”
Section: Resultssupporting
confidence: 92%
“…Several studies have demonstrated the superiority of DES over BMS regarding the need for target-lesion revascularisation [10][11]. In agreement with previous research, in our study, BMS-ISR was significantly more frequent than DES-ISR, but without significant betweenstudy-group differences.…”
Section: Resultssupporting
confidence: 92%
“…Clinical data show the superiority of newer DES in terms of TLR, myocardial infarction and stent thrombosis (ST) (18,19).…”
mentioning
confidence: 99%
“…Whereas in the second group of SG-EES vs. FG-PES less major adverse cardiovascular events were observed (MACE) meaning including death events and myocardial infarction events. In both groups no ST was observed in the EES after the first 3 months [75]. The same positive results were observed with 317 patients again with EES and FG-DESs in another study applying these stents in saphenous vein graft lesions [76].…”
Section: Everolimusmentioning
confidence: 70%